2022
DOI: 10.1111/srt.13153
|View full text |Cite
|
Sign up to set email alerts
|

Objective and automatic grading system of facial signs from selfie pictures of South African women: Characterization of changes with age and sun‐exposures

Abstract: Objective To evaluate the capacity of the automatic detection system to accurately grade, from smartphones’ selfie pictures, the severity of fifteen facial signs in South African women and their changes related to age and sun‐exposure habits. Methods A two‐steps approach was conducted based on self‐taken selfie images. At first, to assess on 306 South African women (20–69 years) enrolled in Pretoria area (25.74°S, 28.22°E), age changes on fifteen facial signs measured by an artificial intelligence (AI)‐based a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…Meanwhile, to continuously improve both the detection and quantification of pigmentary facial signs, previous datasets were annotated by dermatologists with new markers (e.g. Contrast, Size, Spread maculae, Pigmentation of the eye contour) to train the automatic grading to be more holistic and precise 20,29,31 . As in previous collection campaigns, those studies in Brazil, India, Korea and Japan evaluated consumer perception using self‐reported questionnaires on skin and facial appearance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, to continuously improve both the detection and quantification of pigmentary facial signs, previous datasets were annotated by dermatologists with new markers (e.g. Contrast, Size, Spread maculae, Pigmentation of the eye contour) to train the automatic grading to be more holistic and precise 20,29,31 . As in previous collection campaigns, those studies in Brazil, India, Korea and Japan evaluated consumer perception using self‐reported questionnaires on skin and facial appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast, Size, Spread maculae, Pigmentation of the eye contour) to train the automatic grading to be more holistic and precise. 20 , 29 , 31 As in previous collection campaigns, those studies in Brazil, India, Korea and Japan evaluated consumer perception using self‐reported questionnaires on skin and facial appearance. Combining this information with dermatologists' annotations could help improve our predictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 This A.I-based automatic grading system analyses selfie images taken using smartphones and the different datasets used during the development of this algorithm were derived from annotated selfie images from Europe (France, Germany, Spain), North Asia (China, Korea, Japan), India, Brazil, Mexico, Indonesia or the United States. [7][8][9][10][17][18][19] In short, the A.I-based automatic grading system was trained on a scale to predict scores that dermatologists could assess on the same scale.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed and validated an automatic grading system, based on an A.I algorithm, for grading of the severity of 9 facial signs of ageing (including wrinkles and skin texture, ptosis and sagging, vascular signs, pigmentation signs, cheek skin pores), in men and women of different ethnic origins and ages 15,16 . This A.I‐based automatic grading system analyses selfie images taken using smartphones and the different datasets used during the development of this algorithm were derived from annotated selfie images from Europe (France, Germany, Spain), North Asia (China, Korea, Japan), India, Brazil, Mexico, Indonesia or the United States 7–10,17–19 . In short, the A.I‐based automatic grading system was trained on a scale to predict scores that dermatologists could assess on the same scale.…”
Section: Introductionmentioning
confidence: 99%